Decolonizing Or Doing the Best With What We Have? Feminist University-Community Engagement Outside Women’s, Gender, and Sexualities Studies Programs - Tanjeem, Nafisa; Illuzzi, Michael J. (Engaged Scholar Journal, 2022)
Feminist scholars and activists have a long history of integrating feminist praxis in the curriculum through community engagement initiatives. Using feminist critiques, they have investigated possibilities as well as limitations of these initiatives in neoliberal universities (Boyd & Sandell, 2012; Costa & Leong, 2012; Dean et al., 2019; Johnson & Luhmann, 2016; Kwon & Nguyen, 2016). Nevertheless, most of the existing studies focus on feminist community engagement within institutionalized Women’s, Gender, and Sexuality Studies (WGSS) departments, programs, and courses. This article demonstrates how feminist community engagement can expand its scope outside the institutional boundaries of WGSS programs. It contributes to the existing feminist literature in several ways. First, it explores how feminist and decolonial praxis can manifest in a non-WGSS setting and the resulting challenges and possibilities that arise. Second, it argues that the transition from traditional service learning to feminist and decolonial community engagement is a complex, contentious, and iterative process rather than an end goal. Lastly, it elaborates on how faculty can not only avoid the tendency of “learning elsewhere” and framing the community as “unprivileged Other” but also build and organize with community through creative subversion of various structures of the neoliberal university.